2014
DOI: 10.1177/0300060513507648
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low-dose rosuvastatin in patients with type 2 diabetes and hypo high-density lipoprotein cholesterolaemia

Abstract: Objective: To analyse the efficacy of low-dose rosuvastatin for treating hypo high-density lipoprotein (HDL) cholesterolaemia in patients with type 2 diabetes and dyslipidaemia. Methods: Patients with HDL-cholesterol (C) <40 mg/dl and triglycerides (TG) <400 mg/dl who were receiving treatment with lipid-lowering drugs other than rosuvastatin (or previously untreated with lipid-lowering drugs) and with low-density lipoprotein [LDL]-C !120 mg/dl were included. Patients were treated with 2.5 or 5 mg rosuvastatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…6 Recently, many studies found that the low dose of rosuvastatin (ROSV) is more effective to reduce LDL than the high dose, and help treatment of low HDL in patients with type II diabetes and dyslipidemia than other statins. [7][8][9] ROSV is preferred to co-administer with dapagliozin (DAPA) where there is no pharmacokinetic interaction between them so, no need to dose adjustment. 10 In addition, the high-fat high-fructose diet (HFF) in obesity can favor lipid accumulation in liver and kidney, which related to insulin resistance and lipophilicity induced cellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…6 Recently, many studies found that the low dose of rosuvastatin (ROSV) is more effective to reduce LDL than the high dose, and help treatment of low HDL in patients with type II diabetes and dyslipidemia than other statins. [7][8][9] ROSV is preferred to co-administer with dapagliozin (DAPA) where there is no pharmacokinetic interaction between them so, no need to dose adjustment. 10 In addition, the high-fat high-fructose diet (HFF) in obesity can favor lipid accumulation in liver and kidney, which related to insulin resistance and lipophilicity induced cellular damage.…”
Section: Introductionmentioning
confidence: 99%